Global Emergence of Resistance to Fluconazole and Voriconazole in Candida parapsilosis in Tertiary Hospitals in Spain During the COVID-19 Pandemic. (7th November 2022) - Trevijano-Contador, Nuria; Torres-Cano, Alba; Carballo-González, Cristina; Puig-Asensio, Mireia; Martín-Gómez, María Teresa; Jiménez-Martínez, Emilio; Romero, Daniel; Nuvials, Francesc Xavier; Olmos-Arenas, Roberto; Moretó-Castellsagué, María Clara; Fernández-Delgado, Lucía; Rodríguez-Sevilla, Graciela; et al.
Abstract: Background: Candida parapsilosis is a frequent cause of candidemia worldwide. Its incidence is associated with the use of medical implants, such as central venous catheters or parenteral nutrition. This species has reduced susceptibility to echinocandins, and it is susceptible to polyenes and azoles. Multiple outbreaks caused by fluconazole-nonsusceptible strains have been reported recently. A similar trend has been observed among the C. parapsilosis isolates received in the last 2 years at the Spanish Mycology Reference Laboratory. Methods: Yeast were identified by molecular biology, and antifungal susceptibility testing was performed using the European Committee on Antimicrobial Susceptibility Testing protocol. The ERG11 gene was sequenced to identify resistance mechanisms, and strain typing was carried out by microsatellite analysis. Results: We examined the susceptibility profile of 1315 C. parapsilosis isolates available at our reference laboratory between 2000 and 2021, noticing an increase in the number of isolates with acquired resistance to fluconazole, and voriconazole has increased in at least 8 different Spanish hospitals in 2020–2021. From 121 recorded clones, 3 were identified as the most prevalent in Spain (clone 10 in Catalonia and clone 96 in Castilla-Leon and Madrid, whereas clone 67 was found in 2 geographically unrelated regions, Cantabria and the Balearic Islands). Conclusions: Our data suggest that concurrently with the coronavirus disease 2019 pandemic, a selection of fluconazole-resistant C. parapsilosis isolates has occurred in Spain, and the expansion of specific clones has been noted across centers. Further research is needed to determine the factors that underlie the successful expansion of these clones and their potential genetic relatedness.